Tantangan Sertifikasi Halal pada UMKM di Indonesia: Studi Kualitatif terhadap Aspek Sosialisasi, Biaya, dan Regulasi (Lembaga Pengembangan Kinerja Dosen, 2025)
This research uses a descriptive qualitative method to explore the challenges faced by Micro, Small, and Medium Enterprises (MSMEs) in the process of halal certification in Indonesia. Halal certification has become an essential requirement in line with the growing awareness among Muslim consumers regarding the products they consume. However, in practice, many MSMEs remain uncertified due to various obstacles. This study focuses on three main aspects: socialization, cost, and regulation. Interviews with MSME actors reveal that a lack of information and understanding about certification procedures is a major factor behind the low compliance with halal certification requirements. Additionally, the cost of certification, perceived as high by some business owners—particularly those with newly established enterprises—poses a significant barrier. Regulations that are not fully accessible or easily understood also hinder the certification process. Therefore, more active engagement from the government and related institutions is necessary in providing education, financial assistance, and simplifying regulations so that halal certification becomes more accessible to MSME actors throughout Indonesia